(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Fundamental and exploratory research in the field of energetics and rational nature management is currently focused on getting results in the field of the effective development and functioning of energy systems. Such systems are based on modern electrical equipment, including electrical machines and controlled power converters (active rectifiers and regenerative units (AC/DC), direct voltage converters (DC/DC), inverters (DC/AC)), conventional and non-traditional electric power based on renewable energy sources (RES).The Program of basic research in the Russian Federation on a long-term period (2021-2030 years) comprises the actual problems of development of energy supply, energy efficiency, renewable and alternative sources in industry and agriculture, including the issues of production technology, of conversion and storage of electric power.Electric power from the renewable energy sources requires its continuous correction, equalization and buffering i.e. a control system for the system operating modes.The paper presents a project of the power unit that provides both autonomous and traditional operation of a power plant having the possibility of recuperating electrical energy into the network. The structure and the composition of such a power unit is proposed, basic control strategies for an autonomous power generating plant having a capacity of up to 15 kW, operating from the variable low speed engine, also having the other sources of alternative energy with the possibility of power accumulation are considered.